PARP inhibitor olaparib sensitizes cholangiocarcinoma cells to radiation. (26th February 2018) - Mao, Yize; Huang, Xin; Shuang, Zeyu; Lin, Guohe; Wang, Jun; Duan, Fangting; Chen, Jianlin; Li, Shengping
Abstract: Cholangiocarcinoma (CCA) is a highly malignant tumor with resistance to radiotherapy alone. Olaparib, a highly potent poly(ADP‐ribose) polymerase (PARP) inhibitor, has been shown to sensitize many types of tumor to radiotherapy. However, the effect of olaparib, either as monotherapy or as combination therapy with radiotherapy, on CCA is not known, and our study aimed to explore this. To assess radiosensitization in three CCA cell lines (QBC939, HuH28 and TFK‐1), viability and clonogenic assays were conducted. The absorbed radiation doses were 0 Gy, 2 Gy, 4 Gy, and 6 Gy; olaparib concentrations were 0 nmol/L, 1 nmol/L, 10 nmol/L, 100 nmol/L, 1000 nmol/L, 2500 nmol/L, 5000 nmol/L and 10 000 nmol/L. The mechanism of olaparib radiosensitization was explored by Western blotting. Immunofluorescence staining and flow cytometry were conducted to explore DNA damage and apoptosis. The radiosensitivity of CCA cells was enhanced by olaparib, which alone had little effect on the CCA cell lines without BRCA mutations. The degree of radiosensitization increased with increasing doses of olaparib by viability and clonogenic assays in vitro . Olaparib was able to enhance the effect of radiation by inhibiting PARP1, inducing DNA lesions and apoptosis. These findings emphasize the role of olaparib in the radiosensitization of CCA cells. Abstract : We found no significant BRCA1/2 mutations in the cholangiocarcinoma (CCA) cell lines (QBC939, TFK‐1 and HuH28). The degree of radiosensitization is dependent on the doses of olaparib and radiation. Our findings emphasize the role of olaparib in radiosensitization of CCA cells.